(3OQQ GdfMhQ aj eOGFM Gdedc GdefUhQs - (3YHO GdYRjR Hf SQGjG Hf Ydj Hf CHj GdbGSe GdSfHSj GdWGFj GdMdj , Uaj GdOjf,J (B750 (3g` s ((3Ydj Hf fhQGdOjf Hf Ydj s)
(3ChdgG (B:s
(3GdMeO ddg GdPj CWdY fLhe GdeYGfj GdeVjFI aj BaGb NhGWQ GdaUMGA hEf CWjH GdKfGA GdePNhQ QGLY eaQhVg Edi efGbH GdefUhQ s
(3BNQgG (B:s
(3aEf Cgdc abO CHbjJ HYOj ShGQA JYLH GdeJeKdjfG dPjPGJ GdebGWY QGFbGJ dh Cf GdTYQ jdHS dGQJOjfG s
(3fSNI KGdKIs
(3hQO CjVkG JMJ Qbe (B476 (3COHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B8 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B746s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
Keywords: (3GdCOHs